Weathering Words: A Cross-linguistic Analysis of Metaphorical Frames of Climate Change Discourse in English and German Online News Outlets - Nishizaki, Mona (International Journal of Linguistics, 2024)
Climate change is undeniably a major challenge of the 21st century and those to come. While scientists agree on this, the public does not as opinions range from climate change deniers to those who devote their lives to fighting it. News media play a crucial role in shaping the public’s opinion on climate change and as they have a significant influence on the public discourse. This paper offers a cross-linguistic comparison of conceptual climate change metaphors in online news outlets from four different countries and two languages. Using conceptual metaphor analysis, I identified prevalent source domains to conceptualize the causes, effects, and responses to climate change. Overall, I found three shared metaphorical frames: war, destination, and construction, as well as additional metaphors in each language. The analysis revealed war and destination as most dominant source domains through which effects and responses are framed. This suggests news media emphasize the severity of effects and urgency to respond through creating a threatening image of climate change, which we do have the power to fight. The pervasive use of these two metaphors in both languages suggest a common understanding climate change.